Pengaruh Aplikasi Serbuk Biji Mimba Spodoptera litura Nuclear Polyhedrosis Virus dan Varietas Tahan terhadap Perkembangan Ulat Grayak pada Kedelai - Indiati, S. W.; Suharsono, Suharsono; Bedjo, Bedjo (Jurnal Penelitian Pertanian Tanaman Pangan, 2013)
Armyworm Spodoptera litura F. (Lepidoptera: Noctuidae) is an important pest of soybean in Indonesia. Severe damages by this pest can cause yield losses up to 80%. Effectiveness of the armyworm control using Spodoptera litura Nuclear Polyhedrosis Virus (SlNPV), neem seed powder (NSP), and resistant soybean lines was studied in the Laboratory of Entomology, ILETRI, Malang, in 2011. The trial was arranged in a completely randomized design with five treatments and four replications. The treatments consisted two soybean genotypes, Wilis (susceptible variety) and G100H (resistant line) applied with SlNPV and NSP and the leaves were used to feed the armyworm. The results showed that the development of the 3rd instar larvae to the 6th instar caterpillars were influenced by the type of feeds. Sizes of 3rd instar larvae until 6th instar leave fed with leaves of Wilis variety were shorter than those fed with leaves of G 100H. The caterpillars fed with leaves of G100H + 50 g/l SBM reached the 6th instar within 10 days, three days shorter than those fed with leaves of G100H alone. Leaf of Wilis variety also affected the pupal period, caterpillars weight, and pupal weight. Increased of NSP and SlNPV doses on the feed hastened and increased mortality rate of the caterpillars. Caterpillars fed with leaves of G 100H + 2 g/l SlNPV died on the 6th instar. Caterpillars fed with leaves of G100H + 2g/l SlNPV and leaves of G100H + 50 g/l NSP + 2 g/l SlNPV suffered 100% mortality at 9 days after application (DAA), whereas those fed with leaves of G100H + 50 g/l NSP only achieve 97% mortality at 21 DAA. Caterpillars fed with leaves of Wilis variety only showed 27% mortality at 15 DAA or at the pupal phase. Mortality rate of caterpillars fed with leaves of G100H reached 78% at 21 DAA or at the imago phase. Thus, botanical insecticide and SlNPV vegetable could increase effectiveness of resistant soybean in controlling the armyworms.